Control Of Iron In Copper Electrolyte Streams With A New Monophosphonic/Sulphonic Acid Resin (SME Annual Meeting Feb. 28-Mar. 1, Salt Lake City, Utah) - S. S. Xue; M. J. Gula; J. T. Harvey; E. P. Horwitz (Society for Mining, Metallurgy & Exploration, 2000)
A study has been conducted to control iron in copper electrolyte streams using Eichrom Industries’s new Monophosphonic /sulphonic acid resin. The resin strongly and selectively extracts ferric ion over copper and cobalt from highly acidic copper electrolytes. The resin has a loading capacity of 27 g/L of iron and can be readily regenerated. In addition, the new resin can be easily synthesized using commercially available starting materials. This paper presents the experimental results for iron control in copper electrolyte streams using the new resin and discusses its potential applications to other hydro-metallurgical streams.